Desain dan Analisa Maximum Power Point Tracking Pada Sistem Pembangkit Listrik dengan Piezoelektrik - Bannan Khaulah Hanifah; Sujono Sujono (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2019)
In this paper examines the power generation tool using piezoelectric sensors to produce electrical energy sourced from kinetic energy, where the parameters observed are controlled voltage, power, and MPPT design that is made. This study aims to determine the MPPT system commonly used in solar cells to be able to work on different systems using piezoelectric sensors. The system consists of piezoelectric sensor, rectifier circuit, DC-DC converter, PWM, and microcontroller. The discussion of the problem is focused on making renewable energy using kinetic energy through piezoelectric sensors whose voltage will be controlled using the Maximum Power Point Tracking (MPPT) method. Based on the system designed, a piezoelectric output voltage is obtained which is very small, and storage is carried out on the capacitor to obtain a voltage of 3 volts. From this voltage, the MPPT method can’t be done because the voltage on the piezoelectric has decreased dramatically when connected to the DC-DC converter. To get a 3 volt voltage at a mass load of 50 kg it takes 482 seconds with a change in voltage increase of 0.0062 per 1 second, at a load mass of 60 kg it takes 453 seconds with a change in voltage increase of 0.0066 per 1 second, and at a mass of 70 kg it takes 345 seconds with a change in voltage increase of 0.008 per 1 second.